Diferencias y similitudes entre dos cuentos populares islandeses y dos leyendas españolas del siglo XIX - Eleana Andreina Fernández Terán 1995- (2019)
This study, carried out in order to complete the requirements for a title of BA in Spanish, from the University of Iceland, has as its main objective to discuss the differences and similarities between two folktales and two legends written in the XIX century, in Iceland and in Spain. To fulfill this purpose, I analyze in particular the four stories to establish a comparison of these two cultures linked by oral traditions. These oral narratives were later developed into written folktales and legends, published in a historical period characterized by romanticism and realism. The main purpose is to put in evidence how worlds can be related through similar topics represented in texts that demonstrate how peoples evolution can be similar, even if it’s difficult to image that a common denominator could be found between habitants from different territories where history and language are not even shared. From one author to another fascinating actions are narrated, many of them regarding life and death, good and evil, wealth and poverty, etc. While simultaneously in each one of the texts an important moral message is revealed. To summarize, therefore, differences and similarities in the selected texts can allow readers to travel from one country to the other and not realize that they don't ocurre in the same place. Thanks to this study lovers of literature and multiculturalism will discover that these cultural artefacts, from Iceland and Spain, are more similar than different.